ANALISIS PENGARUH PEMBIAYAAN MURABAHAH, MUDHARABAH, DAN MUSYARAKAH TERHADAP PROFITABILITAS BCA SYARIAH DENGAN PERAN COVID-19 SEBAGAI VARIABEL MODERASI - Hanifah Ishma Hanani; Ika Khusnia Anggraini (Islamic Economics and finance in Focus, 2024)
The COVID-19 pandemic which ended in early 2023 affected many sectors throughout the world. Apart from the health sector, Islamic banking also experienced shocks. The problem to be studied in this research is the influence of murabahah, musyarakah and mudharabah financing on the profitability of BCA Syariah by including the role of Covid-19. The aim of this research is to obtain answers to whether these three types of financing partially affect BCA Syariah's profitability, whether the Covid-19 pandemic indirectly affects BCA Syariah's profitability or vice versa. Data analysis uses Moderated Regression Analysis (MRA) because it also considers the role of Covid-19 in this research. Based on the output of this research, the conclusion is that murabahah does not affect BCA Syariah's profitability, unlike mudharabah and musyarakah financing which contribute to increasing BCA Syariah's profitability. The Covid-19 pandemic variable moderates the influence of murabahah and musyarakah financing. However, the pandemic does not affect mudharabah financing activities at BCA Syariah.